TREATMENT OF MALIGNANT ETIOLOGY PLEURISIES USING VIDEOTHORACOSCOPY - S. M. Lazarev; D. V. Alkaz (Вестник хирургии имени И.И. Грекова)
On the basis of an analysis of results of treatment of 123 patients by different methods of pleurodesis the authors have shown advantages of the method of videothoracoscopy.